The role of transposable elements in the evolution of fungal endophyte genomes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Genetics at Massey University, Palmerston North, New Zealand - Smith, Kelli Louise Fukumi (Massey University, 2022)
Transposable elements (TEs) are mobile DNA sequences that can catalyse their own replication and movement within a genome. As a result of their proliferation, TEs have become a major constituent in almost all eukaryotic genomes. While TEs were historically overlooked or dismissed as ‘junk’ DNA, these elements have now been reappraised as important contributors to gene regulation and genome evolution. Markedly, in plant-associated fungi, it has been proposed that TEs regulate expression of genes that mediate the invasion of plants; the localisation of TEs proximal to invasion-mediating genes is proposed to create a niche for accelerated fungal evolution, extending their host-range and assisting in the antagonistic co-evolution with their host plants. Epichloë is a genus of ascomycete fungi that live in close association with pasture grasses. This symbiosis can provide the host plants with profound bioprotective benefits such as increased resistance to drought, herbivory and pests. Hence, there is considerable interest in developing novel Epichloë strains with improved host-range. However, TEs in Epichloë genomes have been considerably inactivated by host genome defences, thus it was unclear whether active elements remain in this genus. In this project, I have curated a high quality library of TEs in three closely related strains of the Epichloë typhina species complex. Using this data, I have demonstrated lineage-specific activity of TEs that have contributed to genome evolution in the recent history of this genus. Furthermore, I have identified sets of TEs that are enriched near virulence-related genes. The work produced here will serve as foundation for future studies to elucidate regulatory roles of TEs in Epichloë.
Keywords: 310509 Genomics